Pre-transplant T-cell clonal analysis identifies CD8+ donor reactive clones that contribute to kidney transplant rejection - Sanders, Jes M.; Banbury, Barbara L.; Schumacher, Erika L.; He, Jie; Sambandam, Yuvaraj; Fields, Paul A.; Gallon, Lorenzo; Mathew, James M.; Leventhal, Joseph R. (Frontiers in Immunology, 2025)
IntroductionResponses to allogeneic human leukocyte antigen (HLA) molecules limit the survival of transplanted organs. The changes in T-cell alloreactivity that contribute to this process, however, are not fully understood. We defined a set of donor reactive T-cell clones (DRTC) with the goal to elucidate signatures of kidney allograft rejection.MethodsDRTC were identified pretransplant using an anti-donor mixed lymphocyte reaction assay: CFSE-diluting CD4+ and CD8+ DRTC were flow-sorted, and the TCR sequences were identified using Adaptive Immunosequencing. DRTC were then tracked in post-transplant biopsies, blood, and urine samples in a cohort of kidney transplant recipients.ResultsIn patients with an abnormal biopsy, the majority of CD8+ DRTC found within the allograft were detected in the circulating pre-transplant repertoire. Circulating CD8+ DRTC were more abundant pre- and post-transplant in patients that received non-lymphodepletional induction and developed an abnormal biopsy when compared to stable patients. Additionally, DRTC were detected as early as two weeks post-transplant in the urine of some patients, with some of these clones subsequently identified in follow-up kidney biopsy samples.DiscussionThe findings of our study add to our understanding of T-cell alloreactivity following kidney transplantation and provide evidence for the role of pre-defined alloreactive T-cells in the development of allograft rejection.